2014
DOI: 10.5057/ijae.13.149
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences in Perception and Attitude towards Robots

Abstract: This study examines the assumptions, perceptions, and attitudes towards contemporary robots in different cultures. As culture affects the way technology is perceived, it is essential to explore the psychological reactions through different cultures towards different designs of robots. Only a few studies have examined attitudes towards robots or dealt with the assumptions in a specific culture. The present study determines the influence of crucial factors like culture, prior exposure to robots through the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 12 publications
2
58
0
1
Order By: Relevance
“…The AIA measure assesses concepts related to AI-related anxiety such as computer anxiety and robot anxiety, and has been utilized in several investigations (e.g. Beckers & Schmidt, 2001;Bolliger & Halupa, 2012;Chu & Spires, 1991;Haring, Mougenot, Ono, & Watanabe, 2014;Heinssen et al, 1987;Hiroi & Ito, 2011;Johnson & Verdicchio, 2017;Nomura et al, 2006;Nomura, Kanda, Suzuki, & Kato, 2008;Ray, Mondada, & Siegwart, 2008;Rosen & Weil, 1995;Wang, 2007;Wu et al, 2014). Computer anxiety is considered to be an irrational fear, apprehension, or phobia that arises following personal interaction with a computer or thinking about using a computer (Herdman, 1983;Howard, 1986;Marcoulides, 1989).…”
Section: Conceptualization Of Aiamentioning
confidence: 99%
See 1 more Smart Citation
“…The AIA measure assesses concepts related to AI-related anxiety such as computer anxiety and robot anxiety, and has been utilized in several investigations (e.g. Beckers & Schmidt, 2001;Bolliger & Halupa, 2012;Chu & Spires, 1991;Haring, Mougenot, Ono, & Watanabe, 2014;Heinssen et al, 1987;Hiroi & Ito, 2011;Johnson & Verdicchio, 2017;Nomura et al, 2006;Nomura, Kanda, Suzuki, & Kato, 2008;Ray, Mondada, & Siegwart, 2008;Rosen & Weil, 1995;Wang, 2007;Wu et al, 2014). Computer anxiety is considered to be an irrational fear, apprehension, or phobia that arises following personal interaction with a computer or thinking about using a computer (Herdman, 1983;Howard, 1986;Marcoulides, 1989).…”
Section: Conceptualization Of Aiamentioning
confidence: 99%
“…The robot anxiety scale (Nomura et al, 2006(Nomura et al, , 2008 is an 11-item, three-subscale (anxiety toward behavioral characteristics of robots, toward discourse with robots, and toward the communication capability of robots) instrument that was designed to measure AI-related anxiety. Other robot anxiety measures include negative images of an assistive robot, negative feelings toward humanoid robots, and root anxiety toward humanoid robots (Haring et al, 2014;Nomura, 2017;Ray et al, 2008;Wu et al, 2014).…”
Section: Conceptualization Of Aiamentioning
confidence: 99%
“…In consequence, Chinese or Japanese users may find it hardly problematic if a machine acquires typically "human" features such as the ability to recognize or express its own feelings; people in the West, on the other hand, are often socialized with a "Frankenstein syndrome" (Kaplan, 2004), therefore considering such technology as a threat to human nature itself (Złotowski et al, 2017). In practice, these arguments-although not entirely unchallenged (Haring et al, 2014)-also offer an explanation for the notably higher acceptance of social robots in countries such as Japan or China (MacDorman et al, 2009;Li et al, 2010;Nomura et al, 2015).…”
Section: Affective Technology Vs Human Uniquenessmentioning
confidence: 99%
“…Despite of the participants were recruited on a special internet forum and Facebook, only 78 active Sony AIBO owners were reached, but the authors believe that sample size was reasonable compared to 230 in [1] and 41 in [13] considering that conducting our survey was long after the product discontinuation. The sampling was not representative for the general public, but the participants could provide a good indication about the typical users of entertainment robots and even beyond this group since Bartneck et al found in [1] that owning a Sony AIBO did not result significantly different scores on their NARS questionnaire.…”
Section: Limitationsmentioning
confidence: 99%
“…The questionnaire was completed by 57 male and 19 female, since two participants did not reveal their gender, with a ratio 73%/24%, similar to another on-line AIBO questionnaire with 64%/36% in [1] and a robotics questionnaire had 61%/39% in [13]. Although there was no question about the income and the wealth of the participants, the authors assume that this rate can be explained with the higher interest of the men in gadgets [12].…”
Section: Questionnairementioning
confidence: 99%